Strategically designed marine reserve networks are robust to climate change driven shifts in population connectivity - Andrew Rassweiler; Elena Ojea; Christopher Costello (Environmental Research Letters, 2020)
Marine reserves can be effective conservation and fishery management tools, particularly when their design accounts for spatial population connectivity. Yet climate change is expected to significantly alter larval connectivity of many marine species, questioning whether marine reserves designed today will still be effective in the future. Here we predict how alternative marine reserve designs will affect fishery yields. We apply a range of empirically-grounded scenarios for future larval dispersal to fishery models of seven species currently managed through marine reserves in the nearshore waters in Southern California, USA. We show that networks of reserves optimized for future climate conditions differ substantially from networks designed for today’s conditions. However, the benefits of redesign are modest: a set of reserves designed for current conditions commonly produces outcomes within 10% of the best redesigned network, and far outperforms haphazardly designed networks. Thus, investing in the strategic design of marine reserves networks today may pay dividends even if the networks are not modified to keep up with environmental change.